Application of atomic force microscopy to assess erythrocytes morphology in early stages of diabetes. A pilot study. (February 2021) - Loyola-Leyva, Alejandra; Loyola-Rodríguez, Juan Pablo; Terán-Figueroa, Yolanda; Camacho-Lopez, Santiago; González, Francisco Javier; Barquera, Simón
Highlights: AFM showed alteration in erythrocyte morphology in those with prediabetes, metabolic syndrome and diabetes. People with prediabetes had a reduction in height and an increase in axial ratio. People with metabolic syndrome had lower concave depth. Diabetes decreased height and concavity, and increased axial ratio and thickness. AFM is a promising instrument to assess erythrocyte morphology changes prior to pathological conditions. Abstract: The study aim was to assess the application of atomic force microscopy (AFM) to evaluate erythrocyte morphology in early stages of type 2 diabetes mellitus, and the association with biochemical, anthropometric, diet, and physical activity indicators. This was a pilot cross-sectional study with four groups: healthy individuals, people with prediabetes (PDG), metabolic syndrome (MSG), and diabetes mellitus group (DMG). Blood samples were obtained to assess the erythrocyte morphology and biochemical parameters. Anthropometrical measurements were taken. Besides, a diet and a physical activity questionnaire were applied. The evaluation of the erythrocyte morphology through the AFM showed quantitative and qualitative alterations in the cell's form and size. Compared to the healthy group, the PDG had a reduction in height (-0.80 μm, p < 0.05), and an increase in axial ratio (-0.09 μm, p < 0.05); the MSG had lower concave depth (-0.19 μm, p < 0.05); and the DMG had a decreased height (-0.46 μm, p < 0.05) and concave depth (-0.29 μm, p < 0.05), and higher axial ratio (+0.08 μm) and thickness (+0.32 μm, p < 0.05). The PDG vs. DMG had a statistically significant difference in concave depth (+0.23 μm, p < 0.05) and thickness (-0.26 μm, p < 0.05). The MSG was different than the DMG in variables like axial ratio (-0.05 μm) and thickness (-0.25 μm). Besides, higher values of age, HbA1c, triglycerides, body mass index, waist-to-hip ratio, and physical inactivity were associated with altered erythrocyte morphology. AFM is a promising instrument to assess early but subtle changes in erythrocyte morphology (height, axial ratio, concave depth, thickness) before significant pathological conditions, such as type 2 diabetes mellitus. HbA1c might have a major effect in altered morphology, vs. metabolic parameters like high triglycerides, body mass index, waist, and physical inactivity.